5-Hydroxy-6-Methyluracil as a Polyvinyl Chloride Stabilizer - Akhmetkhanov, R.M.; Gabitov, I.T.; Mustafin, A.G.; Zakharov, V.P.; Zaikov, G.E. (Journal of Research Updates in Polymer Science, 2015)
Kinetic regularities of thermooxidative dehydrochlorination of rigid and plasticized PVC in the presence of 5-hydroxy-6-methyluracil have been studied. The high antioxidant efficacy of 5-hydroxy-6-methyluracil in the process of polymer degradation has been revealed. It is shown that the studied uracil significantly slows down the process of accumulation of hydroperoxides in oxidation of dioctyl phthalate the plasticizer of PVC, which is the cause of a significant slowdown in the rate of decomposition of the plasticized polymer.